Reporting policies of ISPs: Do general terms and conditions (GTCs) match with the reality? - Nico Grove; Damir Agic; Joachim Sedlmeir (International Telecommunications Society (ITS), 2013)
Technological progress allows Internet Service Providers (ISPs) to carry out network manage-ment practices in a discriminatory fashion without being detected by their customers. This creates an opportunity that providers will exploit this information asymmetry in an opportunistic way by blocking and/or throttling certain services and applications without informing their customers in an adequate fashion that their Internet service is a restricted one. The main objective of this paper is to investigate the extent to which reporting policies - as im-plemented through the General Terms and Conditions (GTCs) - of selected ISPs match with the display of discriminatory behavior by those ISPs as shown by Grove & Agic, (2012). Our analysis examines whether ISPs in Europe and the USA are informing their subscribers adequately about discriminatory traffic management. We, thus, analyze GTCs, signed between ISPs and their subscribers by applying a cross-country/provider approach, focusing on three main aspects of the contractual agreement: (1) availability of service, (2) obligations of the customers and (3) the contractual agreements concerning any intervention in services by ISPs...
Keywords: D22; D63; G13; I38; K23; L86; 330; Network Neutrality; General Terms and Conditions; Regulation; Telecommunications; User Discrimination